HETEROGEJ\TEITY, CONJ\TECTIVITY AND GEOLOGICAL MODELING OF TERTIARY CARBONATE RESERVOIR TN BAI HASSAN OIL FIELD, NORTHERN IRAQ - SADEQ, QAYS MOHAMMED (2016)
Bai Hassan is an elongated, asymmetrical doubly plunging anticline carbonate oil field located near Kirkuk in Northern Iraq. Due to production wells exhibiting great variations, there is a need to quantify heterogeneity in its petrophysical characteristics. The field comprises of two domes separated by an axis-perpendicular, extensional fault reactivated during the Miocene compression Since the fault's throw greater than the Tertiary carbonate reservoir thickness, it should behave as a seal compartmentalizing the reservoir into two domes. However, pressure analysis data indicate a significant communication between the domes. To understand the big difference in the production rates between the wells and the conflict between the geology and pressure data, heterogeneity and connectivity characteristics that require detailed geological analysis.